(untitled) (Global Journal of Management and Business Research, 2019)
Bangladesh is endowed with ample supply of renewable sources of energy. By acknowledging the potential of renewable energy resources, Bangladesh could meet its unprecedented energy demand, thus enhancing electricity accessibility to all and increasing energy security through their progression. A significant number of studies demonstrated the socioeconomic impact of renewable energy, especially in Bangladesh. According to these studies, it is realized that the entrepreneurial perspective of renewable energy is missing except a few studies on innovation theory, social entrepreneurship, and micro-finance. The endeavor of this article is to argue that renewable energy is an opportunity to slow environmental degradation opening a new perspective of the research agenda in entrepreneurship. In addition to that, it is hoped that this article contributes to the connection of entrepreneurial viewpoint, its opportunities and, challenges, with renewable energy in the emerging markets in Bangladesh.